2021
DOI: 10.1186/s41983-021-00413-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological features of SARS-COV-2 associated acute hemorrhagic necrotizing encephalopathy: case report

Abstract: Background The current case report presents acute hemorrhagic necrotizing encephalopathy (AHNE) as an example of a fatal complication, the etiology of which could be coronavirus disease 2019 (COVID-19) with multiple organ damage along with the existing respiratory tuberculosis. Case presentation A male in his 20s had severe symptoms of central nervous system lesion, which developed against the background of COVID-19 and respiratory tuberculosis, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Particularly, we should know if the CSF was investigated for Mycobacterium tuberculosis . Exclusion of tuberculosis is crucial as AHNE has been previously reported in association with cerebral tuberculosis ( Ermilov et al, 2021 ). Arguments for tuberculous meningitis in the index patient are the mild pleocytosis, low CSF glucose, and lactic acidosis.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Particularly, we should know if the CSF was investigated for Mycobacterium tuberculosis . Exclusion of tuberculosis is crucial as AHNE has been previously reported in association with cerebral tuberculosis ( Ermilov et al, 2021 ). Arguments for tuberculous meningitis in the index patient are the mild pleocytosis, low CSF glucose, and lactic acidosis.…”
Section: Letter To the Editormentioning
confidence: 99%
“…With interest we read the article by Ermilov et al about a young male in his twenties, born to a consanguineous marriage, who developed a spontaneous pneumothorax after having been hospitalised in a primary infectious hospital for moderate COVID-19 [1]. Work-up for the cause of pneumothorax revealed "infiltrative pulmonary tuberculosis in the phase of disintegration and seeding" [1]. Consecutively the patient developed impaired consciousness and epilepsy which was attributed to fatal acute, haemorrhagic, necrotising encephalitis (AHNE) [1].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Work-up for the cause of pneumothorax revealed "infiltrative pulmonary tuberculosis in the phase of disintegration and seeding" [1]. Consecutively the patient developed impaired consciousness and epilepsy which was attributed to fatal acute, haemorrhagic, necrotising encephalitis (AHNE) [1]. It was concluded that "the death of the patient, as well as the severity of the disease, was largely due to COVID-19".…”
Section: Letter To the Editormentioning
confidence: 99%
See 2 more Smart Citations